Delay-optimal technology mapping by DAG covering - Kukimoto, Yuji; Brayton, Robert K.; Sawkar, Prashant (DAC 98: DAC: 35th Annual ACM/IEEE Design Automation Conference, 1998)
We propose an algorithm for minimal-delay technology mapping for library-based designs. We show that subject graphs need not be decomposed into trees for delay minimization; they can be mapped directly as DAGs. Experimental results demonstrate that significant delay improvement is possible by this new approach.